Differential larval growth strategies and trophodynamics of larval Atlantic bluefin tuna (Thunnus thynnus) from two discrete spawning grounds - Malca, Estrella; Quintanilla, José M.; Gerard, Trika; Alemany, Francisco; Sutton, Tracey; García, Alberto; Lamkin, John T.; Laiz-Carrión, Raúl (Frontiers in Marine Science, 2023)
Atlantic bluefin tuna (ABT), Thunnus thynnus, is a globally important fishery resource. This oceanic top predator undertakes long-distance migrations from its nutrient-rich feeding grounds in the north Atlantic to oligotrophic spawning grounds. Larvae are born mainly in the corresponding ecosystems of its two well-established spawning areas: the Gulf of Mexico (GoM) and the Mediterranean Sea (MED). Stable isotopes analyses (SIA) of δ15N and δ13C have proven useful for understanding marine food webs and have evaluated larval ABT signatures in their respective spawning areas. This study is among the first to use larvae collected during the same spawning season (2014) from the GoM and one of the main spawning areas within the MED (the Balearic Sea) to standardize methodologies, compare larval growth, and relate SIA with larval postflexion growth using GAMs for the two spawning areas. The main findings identify significant population differences, with comparatively faster growth in GoM larvae. The GoM population had larger otoliths with wider increments, as well as higher δ15N values and higher trophic position for postflexion stages. Collectively, these findings highlight the importance of not only developing well-calibrated growth curves, but also integrating the distinct early life history dynamics for each spawning area to properly support ABT’s ongoing management efforts.